The feasibility of pulsed light processing in the meat industry. (September 2019) - Tomasevic, I; Djekic, I; Novaković, S; Barba, F; Lorenzo, J M
Abstract: Today, the increasing demand for minimally processed foods that are nutritious, sensorially acceptable, and free from microbial, chemical and physical hazards, challenges research and development to establish alternative methods to reduce the level of bacterial contamination. As one of the newly developing non-thermal methods, pulsed light is a technology for the fast, mild, and residue-free surface decontamination of meat and meat contact materials in the meat processing environment. This review provides specific information on pulsed light technology and the feasibility of its application for unpackaged and packaged meat and meat products as well as meat contact materials. The advantages, limitations and achieved effects of pulsed light on microbial inactivation, lipid peroxidation, sensory quality and color of meat, seafood and meat products are illustrated and discussed in relation to its implementation on the industrial level.